Herramientas tecnológicas y el aprendizaje de los estudiantes de la carrera de Comunicación Social de la Universidad Técnica de Babahoyo Extensión Quevedo, año 2019 - Vera Pareja, Milca Priscila (2020)
This case study was carried out in order to analyze and know the influence that technological tools have on the learning of the students of the Social Communication Career of the Technical University of Babahoyo Extension Quevedo. Various theoretical references were taken for the development of the research, which allowed us to deepen and learn a little more about the subject under study, among them we have some of the history and evolution that technological tools have had in society and in the educational field. Also, reference is made to the importance of student interaction with technology for their professional training. To know the current situation and needs of the Social Communication student, quantitative data were collected through the application of surveys. Through which it was possible to draw several conclusions, which expresses the influence of technological tools during the student learning process.